Effects of acute fatigue on the volitional and magnetically-evoked electromechanical delay of the knee flexors in males and females - Minshull, C.; Gleeson, N.; Walters-Edwards, M.; Eston, R.; Rees, D. (European Journal of Applied Physiology, 2007)
Neuromuscular performance capabilities, including those measured by evoked responses, may be adversely affected by fatigue; however, the capability of the neuromuscular system to initiate muscle force rapidly under these circumstances is yet to be established. Sex-differences in the acute responses of neuromuscular performance to exercise stress may be linked to evidence that females are much more vulnerable to anterior cruciate ligament injury than males. Optimal functioning of the knee flexors is paramount to the dynamic stabilisation of the knee joint, therefore the aim of this investigation was to examine the effects of acute maximal intensity fatiguing exercise on the voluntary and magnetically-evoked electromechanical delay in the knee flexors of males and females. Knee flexor volitional and magnetically-evoked neuromuscular performance was assessed in seven male and nine females prior to and immediately after: (1) an intervention condition comprising a fatigue trial of 30-s maximal static exercise of the knee flexors, (2) a control condition consisting of no exercise. The results showed that the fatigue intervention was associated with a substantive reduction in volitional peak force that was greater in males compared to females (15.0, 10.2%, respectively, P < 0.01) and impairment to volitional electromechanical delay in females exclusively (19.3%, P < 0.05). Similar improvements in magnetically-evoked electromechanical delay in males and females following fatigue (21%, P < 0.001), however, may suggest a vital facilitatory mechanism to overcome the effects of impaired voluntary capabilities, and a faster neuromuscular response that can be deployed during critical times to protect the joint system.